Beyond the Shari’ah: Siyasah Shar’iyyah and Its Application - Kamali, Mohammad Hashim (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Beyond the Shari’ah: Siyasah Shar’iyyah and Its Application